Terrorist v Sovereign: Legal performances in a state of exception - N. Rogers (Law Text Culture, 2008)
Stephen Sewell’s (2003) play Myth, Propaganda and Disaster in Nazi Germany and Contemporary America (hereinafter Myth) depicts the fate of Talbot, an Australian academic working in New York, whose outspoken criticism of American complacency in the post–September 11 environment is ruthlessly punished by a representative of the state known only as the Man. The task of the Man is to reveal to Talbot that he, Talbot, is blinded by myth and propaganda, in his case the myth of liberalism and its associated rhetoric of human rights, and that it is in fact violence and power which define truth in contemporary America. The Man identifies himself only as Talbot’s ‘ judge and jury’, his ‘confessor’, with the stated role of ‘facilitat[ing his] return to reality’ (Sewell 2003: 20).